Canonical Correlation Analysis on the Association Between Sleep Quality and Nutritional Status Among Centenarians in Hainan - Guangdong Liu; Shanshan Yang; Wei Liu; Shengshu Wang; Penggang Tai; Fuyin Kou; Wangping Jia; Ke Han; Miao Liu; Yao He (Frontiers Media S.A., 2020)
Objective: To analyze the correlation between nutritional status and sleep quality among centenarians.Methods: A total of 1,002 centenarians in Hainan were included in the full sample survey. The Mini Nutritional Assessment-Short Form (MNA-SF) was used for nutritional risk assessment and the Pittsburgh Sleep Quality Index Scale (PSQI) was used for evaluating sleep quality. Canonical correlation analysis was conducted to analyze their correlation.Results: Two statistically significant (p < 0.05) canonical coefficients were found, with the first canonical correlation coefficient having a value of 0.247, eigenvalue of 0.065, and contribution rate of 89.0%. The linear combination of nutrition variable V1, mainly determined by MNA1 (appetite loss), MNA5 (dementia/depression), and MNA2 (weight loss), indicates an association with sleep quality; the linear combination of sleep quality W1, mainly determined by PSQI1 (subjective sleep quality), PSQI7 (daytime dysfunction), and PSQI2 (sleep latency), indicates an association with nutritional status. Appetite loss, dementia/depression, and weight loss have negative correlations with subjective sleep quality and daytime dysfunction.Conclusion: Among centenarians, the relationship between nutritional status and sleep quality is bidirectional. Furthermore, appetite loss, dementia/depression, weight loss, subjective sleep quality, and daytime dysfunction are the main relevant factors.